Clinical Characteristics, Glycemic Control, and Complications of Type 2 Diabetes Among Employees of Almalyk Mining and Metallurgical Complex. (Uzbekistan Open Conference, 2026)
The Almalyk Mining and Metallurgical Complex (AGMC)is one of the largest industrial complexes in Central Asia; however, there is virtually no data on the clinical and metabolic characteristics of T2D among the workers at this facility. This study aimed to assess the sociodemographic and clinical-metabolic characteristics, the level of glycemic control, the prevalence of diabetic complications and comorbid conditions, and the characteristics of the treatment regimen among 100 AGMC employees with type 2 diabetes. Demographic indicators, occupational history, presence of occupational hazards, anthropometric data, duration of illness, carbohydrate and lipid metabolism indicators, renal function, diabetic complications, cardiovascular comorbidity, ongoing hypoglycemic therapy, as well as the 10-year fracture risk according to the FRAX scale were analyzed from medical records. Men accounted for the majority of the patients examined—82%, while women made up 18%. The mean age of the patients was 51.8 ± 7.9 years. The mean body mass index (BMI) was 29.15 ± 3.32 kg/m². Overweight was identified in 51% of patients, class I obesity in 32%, and clinically significant obesity (BMI ≥35 kg/m²) in 7%. Exposure to occupational hazards (heavy metals, chemical agents, noise, dust) was documented in 76% of patients. Three patients (3%) had a disability classification. The mean duration of type 2 diabetes was 5.4 ± 3.6 years. The mean HbA1c level was 9.63 ± 1.81%. The target HbA1c level of <7.0% was achieved in only 8% of patients. The mean fasting plasma glucose was 7.66 ± 1.38 mmol/L, and the postprandial glucose was 12.44 ± 2.95 mmol/L. The mean total cholesterol was 5.00 ± 0.92 mmol/L. The mean glomerular filtration rate was 104.33 ± 15.24 mL/min/1.73 m², indicating predominantly preserved renal function. The mean FRAX score was 7.13 ± 3.17% (range 2.9–26.0%); in no patient did it exceed the threshold for isolated intervention. Diabetic distal sensory polyneuropathy was detected in all 100 patients (100%). Stage II was predominant (93%); Stage III was present in 6 patients (6.0%), including two cases of diabetic foot syndrome (one with phlegmon). Diabetic retinopathy was diagnosed in 19% of patients. Diabetic nephropathy was present in only 1 patient (1.0%). Cardiovascular comorbidity was highly prevalent: hypertension was detected in 55% of patients, ischemic heart disease in 48%, and chronic heart failure in 66%. In the glycemic control regimen, GLP-2 receptor agonists were used in 59% of patients, metformin in 50%, DPP-4 inhibitors in 17%, insulin therapy in 16%, and sulfonylureas in 4% of patients. A combination of insulin and oral therapy was used in 12% of patients. Adherence to dietary recommendations was observed in only 42% of patients, and 72% had self-monitoring devices (glucose meter and test strips). AGMC employees with type 2 diabetes are characterized by markedly poor glycemic control, a high prevalence of diabetic polyneuropathy, and significant cardiovascular comorbidities.